Hydrolysis of sweet potato (Ipomoea batatas (L.) Lam.) flour by Candida homilentoma strains: effects of pH and temperature using Central Composite Rotatable Design - COELHO,ANA LETÍCIA S. (2020)
Abstract The current study focuses on the evaluation of culture parameters on the enzymatic hydrolysis of Ipomoea batatas (L.) Lam flour by Candida homilentoma strains. A 2-factor-5-level CCRD was used to evaluate the effect of pH and temperature on the hydrolysis process. For the S-47 strain, pH and both studied parameters were significant at 48 h and 96 h, respectively. Regarding S-81 strain, temperature was the only factor affecting the process, at 96 hours. The regression models were significant, and no lack of fit was observed for them.